2017
DOI: 10.21010/ajtcam.v15i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Anti-Inflammatory Activities of Crude Extracts of Three Togolese Medicinal Plants Against Esbl Klebsiella Pneumoniae Strains

Abstract: Background: Pithecellobium dulce (Roxb.) Benth., Securidaca longepedunculata Fresn and Cryptolepis sanguinolenta (Lindl.) Schlt are three plants widely used in the Togolese traditional medicine to treat microbial infections. Some studies reported their antibacterial activity alone but until know there no data concerning their possible interaction with conventional antibiotics. The main objective of this study was to investigate the antibacterial activity of the association of the crude extracts of the three pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Medicinal plants traditionally used for the fight against microbial infection in Togo, Ghana, Benin, Burkina Faso, and Cape-Verde A total of 532 medicinal plants were listed in this study, and the most cited ailments for these plants were diarrhea and infectious diseases in general (Table-1) [52,. A total of 203 medicinal plants were identified in Benin (Figure -1).…”
Section: Status Of Amr In Cape Verdementioning
confidence: 99%
“…Medicinal plants traditionally used for the fight against microbial infection in Togo, Ghana, Benin, Burkina Faso, and Cape-Verde A total of 532 medicinal plants were listed in this study, and the most cited ailments for these plants were diarrhea and infectious diseases in general (Table-1) [52,. A total of 203 medicinal plants were identified in Benin (Figure -1).…”
Section: Status Of Amr In Cape Verdementioning
confidence: 99%
“…Studies has been confirmed that the presence of steroids, saponins, lipids, phospholipids, glycosides, glycolipids, and polysaccharides have been reported in the seeds and bark contains tannins of catechol type and quericitin, kaempferol, dulcitol, and afezilin have been found in the leaves (Kumar, Nehra, & Duhan, 2013). Because of the above mentioned phytochemical constituents it has been reported to be a folk remedy for diabetes, cardiovascular disease, inflammation, oxidative stress, bacterial, viral, and fungal infection (Mule, Naikwade, Magdum, & Jagtap, 2016b;Pal, Pal, Manna, & Sil, 2012;Toudji et al, 2018). In addition, it has been reported to be used as astringent in dysentery, febrifuge, dermatitis, and eye inflammation (Selvan & Muthukumaran, 2011).…”
Section: Health Benefits Of Manilla Tamarindmentioning
confidence: 99%
“…While kale (cruciferous) and Moringa are widely consumed as leafy vegetables, sweet basil is a famous culinary herb. Reports from previous studies have indicated that dietary intake of these plants can have numerous health‐promoting effects like cholesterol‐lowering, anti‐cariogenic, anti‐ulcer, antioxidant, and anti‐bacterial activities due to their exceptional phytochemical profiles (Amrani et al, 2009; Šamec et al, 2019; Toudji et al, 2018). Thus, owing to their high polyphenolic and flavanol content, these plants can be effective in treating obesity‐related disorders by inhibiting the cellular process of adipogenesis.…”
Section: Introductionmentioning
confidence: 99%